2020
DOI: 10.1186/s12877-020-01599-4
|View full text |Cite
|
Sign up to set email alerts
|

Readmission of older acutely admitted medical patients after short-term admissions in Denmark: a nationwide cohort study

Abstract: Background: Knowledge of unplanned readmission rates and prognostic factors for readmission among older people after early discharge from emergency departments is sparse. The aims of this study were to examine the unplanned readmission rate among older patients after short-term admission, and to examine risk factors for readmission including demographic factors, comorbidity and admission diagnoses. Methods: This cohort study included all medical patients aged ≥65 years acutely admitted to Danish hospitals betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
2
21
0
1
Order By: Relevance
“…However, the mortality rates are not negligible, and it is noticeable that patients with pneumonia had a shorter time to death. In a previous study [ 8 ] from our group it was shown that older patients with pneumonia and urinary tract infections had an increased risk of readmission in the 30-day period after discharge. We do not have data on the causes of readmission and death, however, the present results indicate a need for increased focus on patients with these infectious diseases during discharge planning, to optimize treatment and out of hospital care to reduce the risk of complications after discharge.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, the mortality rates are not negligible, and it is noticeable that patients with pneumonia had a shorter time to death. In a previous study [ 8 ] from our group it was shown that older patients with pneumonia and urinary tract infections had an increased risk of readmission in the 30-day period after discharge. We do not have data on the causes of readmission and death, however, the present results indicate a need for increased focus on patients with these infectious diseases during discharge planning, to optimize treatment and out of hospital care to reduce the risk of complications after discharge.…”
Section: Discussionmentioning
confidence: 98%
“…Male gender had in our study a 22% increased risk of death compared to females. Male gender has been associated with many negative health outcomes in older age, including earlier onset of chronic diseases, more readmissions and shorter survival at nursing homes [ 1 , 8 , 19 , 20 ]. Worldwide, men do have shorter lifespan and higher rates of lethal conditions as heart disease and stroke than women, partly due to behavioral differences [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations